2007
DOI: 10.1016/j.cell.2007.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Maps of Drosophila Higher Olfactory Centers: Spatially Segregated Fruit and Pheromone Representation

Abstract: SummaryIn Drosophila, ∼50 classes of olfactory receptor neurons (ORNs) send axons to 50 corresponding glomeruli in the antennal lobe. Uniglomerular projection neurons (PNs) relay olfactory information to the mushroom body (MB) and lateral horn (LH). Here, we combine single-cell labeling and image registration to create high-resolution, quantitative maps of the MB and LH for 35 input PN channels and several groups of LH neurons. We find (1) PN inputs to the MB are stereotyped as previously shown for the LH; (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
782
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 624 publications
(817 citation statements)
references
References 50 publications
31
782
4
Order By: Relevance
“…Molecular, genetic, and neurosensory knowledge in D. melanogaster frames the most complete picture of an olfactory system that is available, from odorant receptor genes to neuroanatomy and central processing of the olfactory input (Couto et al 2005;Benton et al 2007;Jefferis et al 2007;Dickson 2008). A current challenge is to further expand our view to also include odor-mediated behavior that reflects the entire integration pathway from ligand-binding to motor output.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular, genetic, and neurosensory knowledge in D. melanogaster frames the most complete picture of an olfactory system that is available, from odorant receptor genes to neuroanatomy and central processing of the olfactory input (Couto et al 2005;Benton et al 2007;Jefferis et al 2007;Dickson 2008). A current challenge is to further expand our view to also include odor-mediated behavior that reflects the entire integration pathway from ligand-binding to motor output.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 7B) in D. melanogaster reveals a segregation of putative pheromone representing PNs and most other PNs (Jefferis et al 2007). Interestingly, these authors found a high degree of sexual dimorphism in the lateral horn region that emphasise sex-specific integration in the lateral horn that may underlie sex-specific behaviours.…”
mentioning
confidence: 96%
“…In the few comprehensive reconstructions of invertebrates (Daphnia and C. Elegans) the main processes of neurons varied little from animal to animal, but even in isogenic animals, fine details of shape varied among individuals [2,3••,36]. More recent analysis in insects corroborates the idea that single neurons have recognizable arbors but in fine details can be different [33,34]. Few of these studies assayed synaptic connections, but it seems likely that there will be variability there as well.…”
Section: Variabilitymentioning
confidence: 93%